Physical activity questionnaire for older children (PAQ-C) versi Indonesia: confirmatory factor analysis - Indah Prasetyawati Tri Purnama Sari; Muchsin Doewes; Muhammad Furqon Hidayatullah; Awan Hariono (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to adapt the Physical Activity Questionnaire for Older Children (PAQ-C) for Indonesian children aged 9 to 11. It is an analytical survey with a cross-sectional study approach. The instrument was adapted the research developed by Kowalski et al., 1997. It was translated to Indonesian language and also validated by academics of sports science so that the adaptation of the questionnaire was better before the data was collected. The results of the questionnaire adaptation contained the identity of the sample (name, gender, date of birth and age, class, weight, height) and 10 question items. A sample of 401 students, aged 9-11, was collected from urban, suburban, and rural areas. The data analysis used was Confirmatory Factor Analysis (CFA) using LISREL. The results of this study showed that the Standardized Loading Factor (SLF) value in each questionnaire item was >0.5, the Average Variance Extracted (AVE) value was 0.659>0.5, and the Construct Reliability (CR) value was 0.892>0.7. Based on these results, the questionnaire had good convergent validity. Thus, the PAQ-C Indonesian version for ages 9 – 11 was suitable for use. It can be concluded that the measuring instrument can accurately measure the level of children physical activity in urban, suburban, and rural areas, and provide confidence for researchers in Indonesia to use it. Overall, this study emphasizes the importance of a holistic and integrated approach in supporting children's physical activity, which is influenced by the interaction of various layers of the physical and social environment.